Vozes infantis: a caracterização do contraste de vozeamento das consoantes plosivas no português brasileiro na fala de crianças de 3 a 12 anos - Bonatto, Maria Teresa Rosangela Lofredo (2007)
Plosive sounds are produced early in childhood, yet it is not uncommon cases in speech therapy clinics of children who have difficulty pronouncing them, particularly as regards the distinction between voiced and voiceless plosives. Existing literature in Phonetics states that the production of plosives involves the constriction of the vocal folds which can in turn increase the degree of supra-laryngeal obstruction in par with that of sublaryngeal obstruction and, as a result, make voicing difficult. In order to produce voiced obstruent sounds similarly to adults, the child has to learn to synchronize glottal and oral gestures. Procedures for the acoustic investigation of such plosives abound in the literature, among which we can mention Voice Onset Time (VOT), the total duration of the plosive segment and the duration of the vowel sound which either precedes or follows it. The aim of the present study is to characterize, by means of acoustic phonetics investigation, the production of plosive consonants in Brazilian Portuguese (BP), in the speech of three and twelve year-old children. In order to undertake such investigation, we used a corpus comprised of six plosives of BP, extracted from the production of two-syllable words inserted in carrier phrase. The children were selected after detailed analysis and the acoustic sign inspection was carried out in the sound wave shape using the broadband spectrogram. Extractions were made of VOT as well as of each of the vowel and consonant segments from the /a/ sound of diga , besides the key-words, of the word baixinho and the full sentence, starting from the first vowel (ex: D/i/g/a/p/a/p/a/baixinho ). The corpus composed of 3-year-old children was used in the perceptive study with the participation of 120 judges. The results showed that the judges identified the plosives /b/, /d/ e /g/ as voiced when accompanied by at least 53% of sound spectra. As regards /p/, /t/ e /k/, plosives, the appearance of breathy vowel caused these consonants to identified as voiced, while aspiration had no effect whatsoever in the perception of judges in the case of voiceless plosives. As to production results, variability in the mean scores and high standard deviation for voiceless, tonic and post-tonic plosives were observed by and large in all the age brackets. Overall, VOT proved to be a satisfactory parameter for voicing differentiation in infant talk, observed in the speech of children over 3 years of age. However, VOT measures were not consistent enough to differentiate plosives, bilabials and alveolar sounds. This study adopted theoretical notions as proposed by Source - Filter Theory (Fant, 1960), Articulatory Phonology (FAR - Browman and Goldstein, 1986; 1990. 1992) and Articulatory Acoustic (FAAR - Albano, 2001), Direct Realism Theory (Fowler, 1986), and the theory of the phonological system acquisition termed by Albano (1990) as O Toque de Ouvido . Based on this theoretical background, we can affirm that voicing contrast was present in the speech of all the children. We can also affirm that in the production of 3-year-olds there have been greater latency between the coordination of glottal and articulatory gestures, which was observed by the great availability in the productions in the measures of VOT. Velar sounds showed less variability. It was inferred , based on the analysis of spectrographic characteristics along with theoretical foundations of gestural phonology (FAR and FAAR), that small children have difficulty interrupting a gesture and starting another one, probably due to difficulties arisen from overlapping gestures , which are better articulated the older one gets